2018
DOI: 10.15761/cnm.1000105
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the ketogenic diet on psychiatric symptomatology, weight and metabolic dysfunction in schizophrenia patients

Abstract: Objective: The authors aimed to test the effect of a therapeutic ketogenic diet (KD) on the psychotic condition, body composition and metabolic dysfunction in schizophrenic patients, as well as to report the compliance with the diet.Method: Two Ecuadorian schizophrenic patients' male and female (twins) aged 22, were included in a six-week controlled-blinded pilot study under the therapeutic KD. Compliance was determined by daily urine measurements (commercially available ketone strips). Body composition was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Further, impaired prepulse inhibition (PPI) of the startle response (a translationally validated endophenotype of schizophrenia) in the MK-801 NMDA hypofunction model was prevented following ketogenic diet 37 . There have also been case studies suggesting ketogenic diet may be an effective treatment for positive and negative symptoms in schizophrenia and schizoaffective disorder, as well as metabolic dysfunction 38 , 39 . In conclusion, accumulating evidence suggests increases in lactate could be a pathological indicator of bioenergetic defects in cognitive disorders including schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Further, impaired prepulse inhibition (PPI) of the startle response (a translationally validated endophenotype of schizophrenia) in the MK-801 NMDA hypofunction model was prevented following ketogenic diet 37 . There have also been case studies suggesting ketogenic diet may be an effective treatment for positive and negative symptoms in schizophrenia and schizoaffective disorder, as well as metabolic dysfunction 38 , 39 . In conclusion, accumulating evidence suggests increases in lactate could be a pathological indicator of bioenergetic defects in cognitive disorders including schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…This could lead to a possible better disease outcome in reducing symptoms and preventing weight gain with some medications used. The effectiveness of the use of the ketogenic diet on young people at this time was demonstrated, for example, in the case report from Ecuador [16], where in two patients treated for schizophrenia (twins, a woman and a man) after dieting, a reduction in both the PANSS and BMI values in both patients and normalization of liver enzymes in a man. In addition, postmortem studies of the prefrontal cortex and the results of in vivo NMR spectroscopy have shown that there is a bioenergetic dysfunction characterized by abnormal glucose processing and mitochondrial dysfunction, which results in impaired synaptic communication in the brain of people with schizophrenia [17].…”
Section: Dependence Of Diet On the Schizophreniamentioning
confidence: 98%
“…More rigorous and longer term case studies have been conducted ( Table 2 ) in different populations by one of us (C.M.P.) and have provided encouraging results both in terms of symptom control and safety/tolerability ( Palmer, 2017 , 2019b ; Gilbert-Jaramillo et al, 2018 ), which we summarized recently ( Sarnyai et al, 2019 ).…”
mentioning
confidence: 89%